Role of Knowledge Management Methods in Agriculture Need and Approaches - Murthy, A. Krishna; L. S. R. C. V. Ramesh; A. V. S. S. Naga Raju (Journal of Agricultural Extension Management, 2021)
Knowledge Management is the process of collecting, creating, organizing, using and sharing collective knowledge. Knowledge Management mostly refers to tacit or implicit knowledge which is difficult to share in a tangible form. The role of knowledge management in agriculture is critical in addressing the knowledge-intensive farming practices. This paper reviews different knowledge management methods and tools used in agriculture.